Identifying factors affecting sustainable development in sports facilities of Razavi Khorasan Province - Rahmani, H.; Hami, M.; Dosti, M. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
The objective was to identify the factors affecting sustainable development in sports facilities of Razavi Khorasan Province and to design a qualitative model of these factors. The sample of this study consisted of 15 participants (faculty members of sport management, executives of the Ministry of Sport and expert managers of sporting places of Razavi Khorasan Province). In-depth interviews were used as the main data collection tool. In order to analyze the data, the opinions of the experts (text) were coded and categorized. Finally, the identified categories were analyzed according to the conceptual model of research (concepts, components and indicators) and the addition of new components was summarized. This process was carried out with MAXQDA version 18 software. According to the views of the experts analyzed, various factors affect the sustainable development of sports facilities in Razavi Khorasan province. The most important factor was users and the least important factor was privatization. Management, safety, and human resources were also important issues.